Systemic bioavailability and safety of twice-daily topical ozenoxacin 1% cream in adults and children with impetigo. (August 2014) - Gropper, Savion; Cepero, Ana Luisa; Santos, Benjamin; Kruger, Dawie
ABSTRACT: : In this Phase I open-label study, the systemic absorption, clinical response, safety and tolerability of multiple-dose ozenoxacin 1% cream were evaluated in children (≥2 months of age) and adults with impetigo. A single (evening) dose of ozenoxacin 1% cream on day 1 was followed by twice-daily application for 4 days (every 12 h), and then a final single (morning) dose on day 6. A total of 46 patients were enrolled in the study. The majority of ozenoxacin plasma samples were below the limit of quantification (no systemic absorption). Approximately half (22/45) of the evaluable patients achieved clinical success (skin lesions were cured). No patients were withdrawn from the study because of a lack of healing or worsening of a lesion. Ozenoxacin was well tolerated in all patients.